Application of pond to improve river water quality - ., Md Nuruzzaman; Al Mamun, Abdullah; Salleh, Md Noor (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
This paper presents the application of pond to elevate the river water quality by modeling a river through a pond in Water quality Analysis Simulation Program (WASP). Data of a pond located at IIUM, Gombak including its physical and water quality characteristics were used to calibrate the WASP model. It has been revealed that increasing the volume of the pond by increasing its length is more effective than increasing the other dimensions. In the case of Total Suspended Solids removal, increasing the depth proves to be ineffective provided that particle sizes of the suspended solids are less than 0.005mm. A pond having a flow to pond volume ratio of 7 is able to remove 33% of Ammoniacal Nitrogen (AN), 42% of Biochemical Oxygen Demand (BOD) and 50% of Total Suspended Solids (TSS). However, the flow to pond volume ratio demonstrates a descending logarithmic pattern in removing pollutants from the flowing water.